Inflammatory Joint Disease Is a Risk Factor for Streptococcal Sepsis and Septic Arthritis in Mice - Volzke, Johann; Schultz, Daniel; Kordt, Marcel; Müller, Michael; Bergmann, Wendy; Methling, Karen; Kreikemeyer, Bernd; Müller-Hilke, Brigitte; , KoInfekt Study Group (Frontiers in Immunology, 2020)
Septic arthritis is a medical emergency associated with high morbidity and mortality, yet hardly any novel advances exist for its clinical management. Despite septic arthritis being a global health burden, experimental data uncovering its etiopathogenesis remain scarce. In particular, any interplay between septic arthritis and preceding joint diseases are unknown as is the contribution of the synovial membrane to the onset of inflammation. Using C57BL/6 mice as a model to study sepsis, we discovered that Group A Streptococcus (GAS) – an important pathogen causing septic arthritis - was able to invade the articular microenvironment. Bacterial invasion resulted in the infiltration of immune cells and detrimental inflammation. In vitro infected fibroblast-like synoviocytes induced the expression of chemokines (Ccl2, Cxcl2), inflammatory cytokines (Tnf, Il6) and integrin ligands (ICAM-1, VCAM-1). Apart from orchestrating immune cell attraction and retention, synoviocytes also upregulated mediators impacting on bone remodeling (Rankl) and cartilage integrity (Mmp13). Using collagen-induced arthritis in DBA/1 ˣ B10.Q F1 mice, we could show that an inflammatory joint disease exacerbated subsequent septic arthritis which was associated with an excessive release of cytokines and eicosanoids. Importantly, the severity of joint inflammation controlled the extent of bone erosions during septic arthritis. In order to ameliorate septic arthritis, our results suggest that targeting synoviocytes might be a promising approach when treating patients with inflammatory joint disease for sepsis.